Synthesis of cinnamoyl-amino acid ester derivatives and structure-activity relationship based on thermal stability, dielectric, and theoretical analysis - GÖRGÜLÜ, AHMET ORHAN (My University, 2022)
In this study, cinnamic acid derivatives were synthesized from the reaction of benzaldehyde derivatives with malonic acid in the presence of pyridine and piperidine. These compounds were then respectively reacted with glycine and L-alanine methyl ester hydrochloride based on triazine methodology to obtain novel cinnamoyl-amino acid ester derivatives. The structure of these compounds were established via H-1, C-13 APT, FT-IR, MS and elemental analysis. The synthesized novel compounds were studied in terms of structure-activity relationship based on dielectric, thermal stability, and theoretical analysis. Dielectric analysis was carried out in terms of amino acid type and aromatic substituted group (electron-withdrawing or releasing group factor). Amino acid side chain differences make alanine conjugates have higher epsilon \" values compared to glycine conjugates. Thermal stability analysis was performed for the compounds (10 and 16) with the highest dielectric constants. Thermal decomposition activation energies were calculated as 95 kJ mol(-1) and 100 kJ mol(-1) for 10 and 16, respectively. HOMO-LUMO energy levels and other related properties of the target compounds were analyzed and a correlation was observed between HOMO-LUMO energy band gap and dielectric constant.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Amino acid; Cinnamic acid; Dielectric; Structure-activity; Thermal stability; OPTICAL-PROPERTIES; ABSOLUTE HARDNESS; CARBOXYLIC-ACIDS; BEHAVIOR; SPECTROSCOPY; CHLORIDES; FILMS